2022
DOI: 10.3389/fneur.2022.995875
|View full text |Cite
|
Sign up to set email alerts
|

Atypical acute disseminated encephalomyelitis with systemic inflammation after a first dose of AztraZaneca COVID-19 vaccine. A case report

Abstract: BackgroundOnly a few cases of acute disseminated encephalomyelitis (ADEM) following coronavirus disease 19 (COVID-19) vaccination have been described since the beginning of the vaccination campaign.ResultsHere we report the first case of central nervous system (CNS) demyelination with systemic inflammatory findings on whole body 19-fluorodeoxyglucose positron emission tomography with computed tomography (FDG-PET/CT) following the ChAdOx1 nCoV-19 vaccine.ConclusionsClinicians should stay aware of potential new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…A systematic review has been identified (8) including 20 studies, out of which 19 were eligible to be included in our review: (9,10,(19)(20)(21)(22)(23)(24)(25)(26)(27)(11)(12)(13)(14)(15)(16)(17)(18) (Figure 1) In addition to the 19 studies included, our literature search has identified nine other studies: (28)(29)(30)(31)(32)(33)(34)(35). Thus, a total of 28 studies were analysed comprising a total of 38 cases.…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review has been identified (8) including 20 studies, out of which 19 were eligible to be included in our review: (9,10,(19)(20)(21)(22)(23)(24)(25)(26)(27)(11)(12)(13)(14)(15)(16)(17)(18) (Figure 1) In addition to the 19 studies included, our literature search has identified nine other studies: (28)(29)(30)(31)(32)(33)(34)(35). Thus, a total of 28 studies were analysed comprising a total of 38 cases.…”
Section: Resultsmentioning
confidence: 99%
“…The key therapy for severe patients includes IVIG, steroids, and plasma exchange [ 100 ]. ADEM usually presents as a monophasic course, although a few recurrent cases have been reported [ 104 ]. Fortunately, most patients have a good prognosis after treatment, with a few fatal cases [ 102 ].…”
Section: Discussionmentioning
confidence: 99%